Author's reply to the commentaries: Clearing up misunderstandings about the course-of-experience framework and laying the groundwork for future discussions. (April 2023) - Poizat, Germain; Flandin, Simon; Theureau, Jacques
In the context of this special issue on the course-of-experience framework, we were fortunate to receive far-reaching commentaries from a wide variety of disciplines including enaction, phenomenology, ecological psychology, ecological dynamics, cognitive anthropology and archaeology and the philosophy of mind. The result is an extraordinarily rich set of reflections that critically engage in debate and lay the groundwork for future discussions and empirical research. In this reply, the authors try to highlight the originality of the course-of-experience framework, which is not yet widely known but has the potential to offer a breakthrough in the present-day international ecological-enactive mainstream and an alternative to (Husserlian) phenomenologically inspired enactivist approaches. They also try to set things right concerning the critical dimensions of cognitive ecology, such as the role of material and 'others' that they didn't mention in their original article (in view of the objectives pursued).